The Function of NF-Kappa B During Epilepsy, a Potential Therapeutic Target - Cai, Mengtan; Lin, Weihong (Frontiers in Neuroscience, 2022)
The transcriptional regulator nuclear factor kappa B (NF-κB) modulates cellular biological activity by binding to promoter regions in the nucleus and transcribing various protein-coding genes. The NF-κB pathway plays a major role in the expressing genes related to inflammation, including chemokines, interleukins, and tumor necrosis factor. It also transcribes genes that can promote neuronal survival or apoptosis. Epilepsy is one of the most common brain disorders and it not only causes death worldwide but also affects the day-to-day life of affected individuals. While epilepsy has diverse treatment options, there remain patients who are not sensitive to the existing treatment methods. Recent studies have implicated the critical role of NF-κB in epilepsy. It is upregulated in neurons, glial cells, and endothelial cells, due to neuronal loss, glial cell proliferation, blood-brain barrier dysfunction, and hippocampal sclerosis through the glutamate and γ-aminobutyric acid imbalance, ion concentration changes, and other mechanisms. In this review, we summarize the functional changes caused by the upregulation of NF-κB in the central nervous system during different periods after seizures. This review is the first to deconvolute the complicated functions of NF-κB, and speculate that the regulation of NF-κB can be a safe and effective treatment strategy for epilepsy.